Peningkatan Kapabilitas Inovasi Teknis dan Bisnis Melalui Pendampingan di KOBAMIE Jaya Kendal - Kemal Budi Mulyono; M. Fathur Rahman (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
Innovation plays an essential role in business processes. Therefore, every entrepreneur must understand the critical characteristics of his business so that he is able to determine the direction of business innovation that the company will develop. Based on this, this service aims to increase the business innovation capabilities of cake and noodle artisans who are members of JAYA's KOBAMIE (Bakery and Noodle Cooperative) located in Weleri District, Kendal Regency. This activity was carried out using both technical training methods related to the development of noodle product innovation and bread product innovation with sources from PT Sriboga Ratu Raya. Meanwhile, business innovation training was delivered by the Faculty of Economics team at Semarang State University. This activity received a positive and enthusiastic response from KOBAMIE JAYA Members so it is hoped that entrepreneurs can compete superiorly through technical and business innovation assistance in this series of community service activities. Furthermore, it is also expected that after carrying out this service process, it will be able to increase innovation capabilities in the cake and noodle maker business that are members of KOBAMIE JAYA, Kendal Regency.